Group B Streptococcus screening in pregnant women: integrative review (Revista Científica Integrada, 2024)
Objective: To identify the best prenatal screening methods for preventing Group B Streptococcus (GBS) perinatal infection in pregnant women. Methods: An integrative review conducted on LILACS, PubMed, CINAHL databases, and SciELO and BVS virtual libraries, using the terms " Group B Streptococcal Infection", "Pregnant Women" and "Screening". Research was conducted in March 2024 for articles from the last ten years, in English, Portuguese, or Spanish. Results: From 535 identified works, 14 articles were selected, focusing on the efficacy, cost, and ease of use of molecular diagnostic methods for GBS screening. Findings suggest that real-time PCR and other rapid molecular methods are superior to the gold-standard bacterial culture in terms of speed and accuracy. Conclusion: Integrating advanced diagnostic methods can significantly enhance strategies for preventing GBS vertical transmission. The sociocultural characteristics and risk factors of the screened populations should be considered for more specific management and treatment.
Keywords: Group B Streptococcal Infection; Pregnant Women; Screening